"Living on the world": rethinking justice by reconsidering vulnerability and autonomy - Danani, Carla (Medicina e Morale, 2020)
In this article, I propose a unitary vision that links vulnerability and autonomy together. The aim is to rethink a number of crucial issues related to justice. Firstly, I undertake an in-depth consideration of human vulnerability. By human beings, I understand instances of "embodied consciousness", who inhabit the placedness of the world not simply by living in it but also by living on it. Openness, exposure and exchange are ontological features through which human beings both receive and cause harm and injuries, but also receive and cause enjoyment and fulfillment. Secondly, I point out that the condition of human interdependency does not require us to give up the demand to pursue "autonomy". On the contrary, autonomy needs to be rethought, by presenting it as something that is constitutively relational. Finally, I argue for the centrality of issues concerning justice, for human beings develop by constantly establishing relations with human and non-human alterities. The model of subordination, though, should be avoided. My aim is to go beyond the sterile opposition between context perspectives emphasized by care ethics and universalistic approaches endorsed by the ethics of rights. The goals are to build a world where everyone can live one's ontological inter-dependency without paternalism or subordination, can be protected from avoidable vulnerabilities and have the opportunity to develop and to perform one's autonomy. This raises issues about the distribution of goods in the social-economic sphere, but also on the management of social infrastructures and the recognitional practices in societies: which are all always placed.